If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3m=(-6)
We move all terms to the left:
3m-((-6))=0
We add all the numbers together, and all the variables
3m+6=0
We move all terms containing m to the left, all other terms to the right
3m=-6
m=-6/3
m=-2
| a^2+(a+3)^2=45 | | 52(a-7)=11a+5 | | 3y=7y+16 | | 9b^2-2=34 | | 11=w-9w=4 | | 10=6x=22 | | 8(6x+5)=20-8x | | -2=b-23 | | 49+3h=-23 | | (s+6)(s+7)=2 | | (x-7)(x+183)=(3x-10) | | 2v^2-9v-35=0 | | -k=81 | | 6(-2x+4)=96 | | x+7/8=1/2 | | 6a+(7)=3a7+2a | | x+122+114=180 | | -9c=-63 | | 12y+36=144 | | 7x+2=2x-5+X | | |n|=3.5 | | 0.1x=0.2(x.2) | | -x-15=2x+3 | | x2−5x−28=8 | | 95=m+10 | | -5(-x-3)-2(x-4)=-4 | | 10=2=x | | |7+4w|=13 | | -2n+2=3n=17 | | 2(3x-4)-4(1-6x)=18 | | 13b-6=2b+8 | | 5p+90=20-2p |